BUGIS CULTURAL PHILOSOPHY MALEMPU NA MAPACCING IN REALIZING FRAUD-FREE VILLAGE FUNDS - Sahriani Saleha; Haliah; Andi Kusumawati (Universitas Islam Negeri Alauddin Makassar, 2022)
Abstrac, Budget allocations that do not correspond to the priority level of needs and reflect only slightly the level of activity, efficiency and economy. This study aims to review the cultural philosophy of bugis malempu na mapaccing in realizing fraud-free village funds. This research is a literature review, descriptive analysis. The result of this study is that managing finances in accordance with the Principles of Good Governance is a sign that the agency has carried out management in accordance with the rules set by the government. The principle of Good Governance has 3 basics, namely transparent, accountable and participatory and carried out according to the budget discipline rules. Behaving malempu na mapaccing is the right way to be applied in managing finances. Malempu na Mapaccing can be useful for suppressing fraud that can harm yourself and society. In addition, cheating is also an act that is contrary to the truth, because it is carried out deliberately by parties who want to obtain profits that are not their right. Abstrak, Alokasi anggaran yang tidak sesuai dengan tingkat prioritas kebutuhan dan hanya sedikit mencerminkan tingkat kegiatan, efisiensi dan ekonomi. Penelitian ini bertujuan untuk meninjau falsafah budaya bugis malempu na mapaccing dalam mewujudkan dana desa bebas fraud. This research is a literature review, descriptive analysis. Hasil dari penelitian ini yaitu Mengelola keuangan yang sesuai dengan Asas Good Governance merupakan suatu tanda bahwa instansi tersebut telah melakukan pengelolaan yang sesuai dengan aturan yang telah ditetapkan oleh pemerintah. Asas Good Governance memiliki 3 dasar yaitu transparan, akuntabel dan partisipatif serta dilakukan sesuai tata tertib disiplin anggaran. Berperilaku malempu na mapaccing merupakan cara yang tepat untuk diterapkan dalam mengelola keuangan. Malempu na Mapaccing dapat berguna untuk menekan tindak kecurangan yang dapat merugikan diri sendiri dan masyarakat. Selain dari itu, kecurangan juga merupakan suatu perbuatan yang bertentangan dengan kebenaran, karena dilakukan secara sengaja oleh pihak yang ingin memperoleh keuntungan yang bukan merupakan haknya.